2022
DOI: 10.1177/21925682221120788
|View full text |Cite
|
Sign up to set email alerts
|

Weekend Admission Increases Risk of Readmissions Following Elective Thoracolumbar Spinal Fusion

Abstract: Study Design Retrospective database study. Objectives The goal of this study was to assess the influence of weekend admission on patients undergoing elective thoracolumbar spinal fusion by investigating hospital readmission outcomes and analyzing differences in demographics, comorbidities, and postoperative factors. Methods The 2016-2018 Nationwide Readmission Database was used to identify adult patients who underwent elective thoracolumbar spinal fusion. The sample was divided into weekday and weekend admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…We also explored differences associated patient readmissions to hospital as a secondary process outcome. Unlike Rosenberg et al 36 who found that 30‐day readmissions were significantly greater for patients undergoing a specific elective surgery procedure admitted at the weekend, we observed no clear after‐hours effect for our 30‐day readmission models. However, there were a number of significant case‐mix interactions, and socioeconomic disadvantage and DRG complexity are persistent interactions in the “Extended” and “Twilight” models.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We also explored differences associated patient readmissions to hospital as a secondary process outcome. Unlike Rosenberg et al 36 who found that 30‐day readmissions were significantly greater for patients undergoing a specific elective surgery procedure admitted at the weekend, we observed no clear after‐hours effect for our 30‐day readmission models. However, there were a number of significant case‐mix interactions, and socioeconomic disadvantage and DRG complexity are persistent interactions in the “Extended” and “Twilight” models.…”
Section: Discussioncontrasting
confidence: 99%
“…We also explored differences associated patient readmissions to hospital as a secondary process outcome. Unlike Rosenberg et al 36 F I G U R E…”
Section: Notementioning
confidence: 86%
“…6,7 Studies have found weekend admission to be associated with higher risk of mortality, cost, increased length of stay (LOS), and worse outcomes in patients undergoing spine procedures for idiopathic scoliosis, 8 cervical fusion due to trauma, 9 and thoracolumbar fusion. 10 However, other studies have found no association between index weekend admission and complication or mortality rates in emergent spinal cord injury patients. 11 Although risk factors for readmission in patients undergoing cervical spinal fusions have been identified, 12 the day of surgery was not considered.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 97%
“…To our knowledge, weekend admission has only been described as a risk factor for 30-day readmission in the context of posterior cervical spine surgery and thoracolumbar spine fusion. 10,12 A study using 2014 NRD data for ACDF subjects suggest payor status, NRD, comorbidities, and LOS are significant predictors for readmission, but weekend admission was not found to be a risk factor for readmission rates. 25 Other studies identify payor status and race, 26 and all-cause complications, Medicaid insurance, hospital bed size, and age, 27 as predictors for high readmission rates.…”
Section: Readmission Ratesmentioning
confidence: 99%
See 1 more Smart Citation